A new geometric shape-based genetic clustering algorithm for the multi-depot vehicle routing problem - Yucenur, G. Nilay; Demirel, Nihan Cetin (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this paper, a new type of geometric shape based genetic clustering algorithm is proposed. A genetic algorithm based on this clustering technique is developed for the solution process of the multi-depot vehicle routing problem. A set of problems obtained from the literature is used to compare the efficiency of the proposed algorithm with the nearest neighbor algorithm so as to solve the multi-depot vehicle routing problem. The experimental results show that the proposed algorithm provides a better clustering performance in terms of the distance of each customer to each depot in clusters. This result in a considerably less computation time required, when compared with the nearest neighbor algorithm. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Multi-depot vehicle routing problem; Genetic algorithm; Genetic clustering; The nearest neighbor algorithm; FUZZY C-MEANS; ANT COLONY OPTIMIZATION; TABU SEARCH; K-MEANS; TARDINESS; Computer Science; Engineering; Operations Research & Management Science